Self-assembled spheres, flowers, and fibers from the same backbone and similar side chains - Singh, Anup Kumar; Krishnamoorthy, Kothandam (Langmuir, 2017)
Rylene imides (Ms) self-assemble into various nanostructures. Often, the synthesis of unsymmetrical RIs (URIs) is required to achieve nanostructures. However, the synthesis of URIs is nontrivial. Thus, a structurally similar alternative is desirable. iso-Indigo (i-indigo) has a pi core and lactam rings that are structurally similar to the RIs. Unsymmetrical iso-indigo (i-indigo) can be easily synthesized by condensing oxindole and isatin. We have synthesized a series of unsymmetrical i-indigo molecules. In these molecules, the pi-pi interaction, hydrogen bonding, and van der Waals interactions are in operation. Because of these, the molecules self-assemble into spheres, fibers, and dahlia flower morphologies. If the hydrogen bonding interaction is disrupted, then all of them form fibers. Control experiments indicate that the complete absence of hydrogen bonding is deleterious to self-assembly. We also show that the lower analogs of i-indigo are not sufficient to form self-assembled nanostructures.

Solvatochromism and side chain effects on the morphological behavior of bodipy-alt-i-Indigo copolymers - Singh, Anup Kumar; Swain, Gitanjali; Birajdar, Sarika (New Journal of Chemistry, 2024)
Among the factors that govern the self-assembly of a molecular system, side chains and solvent polarity play crucial roles in the morphological alteration of small molecules in solutions. Although the effect of side chains on the self-assembly of small molecules has been studied well, reports on their importance in the aggregation behavior of polymers are limited. Investigating whether a minor change in the side chain produce any significant impact on the morphology of the polymer in solution is of great research interest. Towards the end goal, to alter the morphology of polymers and to know the impact of the side chains on the self-assembly properties of the conjugated polymers, two BODIPY-i-Indigo alternating copolymers, P1 [poly(BDP12-alt-iI)] and P2 [poly(BDPE-alt-iI)], were synthesized, and their aggregation behavior was explored in various solvents. Both the copolymers, P1 and P2, exhibited narrow PDI values of 1.16 and 1.45, respectively. Although their cores are the same, P1 showed a thin film morphology, while P2 displayed a porous morphology (approximately 557 nm) in chloroform. On changing the solvent, P1 showed a porous morphology in a 50% THF-CHCl3 mixture. However, in P2, the pores were reduced to extremely small sizes in the 50% THF-CHCl3 mixture. This work demonstrates that even a minimal change in the side chains of copolymers and polarity differences between solvents can produce a drastic morphological effect.